A Cross-Sectional Multicentre Study to Validate Insulin Sensitivity Index Cut-Offs for Detection of Metabolic Syndrome in Indian Adolescents with Type-1 Diabetes - Oza, Chirantap; Khadilkar, Anuradha; Mondkar, Shruti; Amutha, Anandakumar; Uppal, Saurabh; De, Hriday; Ghosh, Apurba; Khadilkar, Vaman; Mohan, Viswanathan (Indian journal of endocrinology and metabolism, 2023)
Background: A previous study compared insulin sensitivity indices for the detection of double diabetes (DD) in Indian adolescents with type-1 diabetes (T1D) and derived a cut-off to predict future risk for the development of metabolic syndrome (MS) in adolescents with T1D. We conducted the current study with the aim to validate these cut-offs for detecting DD among Indian subjects with T1D from various geographical locations. Methods: This multicentric cross-sectional study included 161 Indian adolescents with T1D. Demographic, anthropometric, clinical, and biochemical data were collected using standard protocols. Insulin sensitivity (IS) was calculated using various equations developed to determine insulin sensitivity in subjects with T1D. Metabolic syndrome was diagnosed using International Diabetes Federation (IDF) Consensus Definition 2017. Results: We report 4.3% prevalence of MS in Indian adolescents with T1D with an additional 29.8% of study participants at risk of development of MS. Low High density lipoprotein (HDL) (23.6%) was the commonest abnormal component of the MS definition. Insulin sensitivity calculated by an equation derived by the SEARCH group was the most appropriate index to identify MS and metabolic risk in Indian adolescents with T1D. The proposed cut-off of 5.48 had high specificity, positive predictive value, and negative predictive value in identifying the risk of the development of DD. Conclusions: Insulin sensitivity calculated by the equation proposed by the SEARCH group together with cut-offs derived in earlier study may be used effectively to identify risk of development of MS/DD in Indian adolescents with T1D from various geographical locations.